(untitled) (Research, Society and Development, 2025)
Over-the-counter drugs (OTCs) are products sold to treat self-limiting illnesses, but their irrational use can lead to health problems. This study aimed to assess the perception of the population of the Maguari neighborhood, in Ananindeua City, Pará (PA) State, regarding the use of these medications. A qualitative-quantitative survey was conducted with 100 participants. The results showed that self-medication is prevalent, being more common among women (69%) than men (31%). The age group between 18 and 35 years old was the most frequent user of OTCs (35%). Considering educational level: education, participants with a high school diploma (50%) and graduates (34%) reported using these medications. Additionally, 59% were unaware of what OTCs are. The research revealed that 78% purchase OTCs without professional guidance. The main reason for the purchase was the presence of specific symptoms. Although 90% did not report health problems resulting from the use of OTCs, 10% mentioned complications. About 54% believe that information about OTCs is insufficient, and 62% support stricter sales restrictions. 30% did not receive guidance on usage, but 75% recognized the importance of pharmaceutical advice. The majority, 93%, agree on the need for rational use of these medications to ensure treatment safety. These data justify the importance of guiding the appropriate use of OTCs to avoid health risks. To mitigate risks, it is important to have educational campaigns and encourage consultations with healthcare professionals, especially pharmacists.